Project “National Research University” – Driver of Russian Higher Education - A. V. Berestov; A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev; S. M. Sadchikov (Высшее образование в России)
The article presents the results of the national research universities (NRU) development programs implementation analysis for the period 2008–2018. The authors have held a comparative analysis of NRU activities with other strategic initiatives in the field of higher education in Russia, in particular, Russian Academic Excellence Project 5-100 on Competitiveness Enhancement of the Leading Russian Universities among Global Research and Education Centers; Project «Federal Universities»; support for strategic development programs of state educational institutions of higher education; sustainable relationships support between higher educational institutions and regional enterprises and organizations within the framework of the priority project “Universities as Innovation Drivers”. The analysis was based on 41 quantitative and 11 qualitative indicators. In the analysis, the following data sources were used: statistical forms 1-Monitoring, data from ranking agencies, etc. It has been determined that implementation of development programs for the entire NRU network is generally successful and positively affects the development of Russian higher education. The leading NRU – the participants of Project 5-100 have shown the greater impact on the enhancement of the Russian education in the world.